Vedolizumab Therapy in Severe Pediatric Inflammatory Bowel Disease. Issue 10 (October 2016) - Conrad, Máire A.; Stein, Ronen E.; Maxwell, Elizabeth C.; Albenberg, Lindsey; Baldassano, Robert N.; Dawany, Noor; Grossman, Andrew B.; Mamula, Petar; Piccoli, David A.; Kelsen, Judith R.
Abstract : Background: Vedolizumab is effective for inducing and maintaining remission in adults with inflammatory bowel disease (IBD); however, there is limited pediatric data. This study aimed to describe the adverse events and clinical response to vedolizumab in refractory pediatric IBD. Methods: Disease activity indices, clinical response, concomitant medication use, and adverse events were measured over 22 weeks in an observational prospective cohort study of children with refractory IBD who had failed anti–tumor necrosis factor therapy and subsequently initiated vedolizumab therapy. Results: Twenty-one subjects, 16 with Crohn disease, received vedolizumab. Clinical response was observed in 6/19 (31.6%) of the evaluable subjects at week 6 and in 11/19 (57.9%) by week 22. Before induction, 15/21 (71.4%) participants were treated with systemic corticosteroids, as compared with 7/21 (33.3%) subjects at 22 weeks. Steroid-free remission was seen in 1/20 (5.0%) subjects at 6 weeks, 3/20 (15.0%) at 14 weeks, and 4/20 (20.0%) at 22 weeks. There was statistically significant improvement in serum albumin and hematocrit; however, C-reactive protein increased by week 22 ( P < 0.05). There were no infusion reactions. Vedolizumab was discontinued in 2 patients because of severe colitis, requiring surgical intervention. Conclusions: There is limited experience with vedolizumab therapy in pediatric IBD. There seems to be a marked number of subjects with clinical response in the first 6 weeks that increases further by week 22 despite the severity of disease in this cohort. Adverse events may not be directly related to vedolizumab. This study is limited by small sample size, and larger prospective studies are warranted. Abstract : Article first published online 6 September 2016.